5
$\begingroup$

merry Christmas to all the users!

I want to get to $\mathbf H =\dfrac{\mathbf B}{\mu_0}-\mathbf M$ from the superposition principle, like some texts have done in electrostatics with $\mathbf D=\epsilon_0\mathbf E+\mathbf P$. In magnetostatic I'm stuck.

For example, in electrostatics, by the superposition principle, the potential outside of a polarized body must be the sum of the potentials due to free and bound charges. When applying the gradient it results \begin{array}{cl}\boldsymbol\nabla V=\boldsymbol\nabla V_\text{l}+\boldsymbol\nabla V_\text{p}&(1)\end{array}

The total field will be given by the total electric potential (again, by the ppio of superposition), so that $\mathbf E=-\boldsymbol\nabla V$. If we apply the gradient (with respect to the coordinates of $\mathbf r$) to \begin{equation} V_\text{p}\left(\mathbf r\right)=k_e \displaystyle\int_V\dfrac{\mathbf P\left(\mathbf r^{\prime}\right)\cdot\hat{\mathbf R}}{R^2}\ \mathrm{d}\tau^{\prime} \end{equation}

we will obtain the electric field due to the polarization: \begin{array}{rcl}\boldsymbol\nabla V_p&=&\boldsymbol\nabla\left(k_e \displaystyle\int_V\dfrac{\mathbf P\left(\mathbf r^{\prime}\right)\cdot\hat{\mathbf R}}{R^2}\mathrm{d}\tau^{\prime}\right)=k_e \displaystyle\int_V\mathbf P\left(\mathbf r^{\prime}\right)\cdot\underbrace{\boldsymbol\nabla\left(\dfrac{\hat{\mathbf R}}{R^2}\right)}_{4\pi\delta^3\left(\mathbf R\right)}\mathrm{d}\tau^{\prime}\\&=&\underbrace{4\pi k_e }_{1/\epsilon_0}\displaystyle\int_V\mathbf P\left(\mathbf r^{\prime}\right)\delta^3\left(\mathbf r-\mathbf r^{\prime}\right)\mathrm{d}\tau^{\prime}=\dfrac{\mathbf P\left(\mathbf r\right)}{\epsilon_0}\end{array}

Substituting in $(1)$ and multiplying the equation by $\epsilon_0$ results \begin{equation}\epsilon_0\mathbf E+\mathbf P=-\epsilon_0\boldsymbol\nabla V_l\end{equation}

The member on the left is usually abbreviated by \begin{equation}\mathbf D=\epsilon_0\mathbf E+\mathbf P\end{equation} which we called displacement vector.

In magnetostatics I have not seen in books that they do that in this way, if not by adding the currents of magnetization and free. Although this serves I would like to do it by the superposition principle and I would want to do the same:

Starting from \begin{array}\mathbf A_\text{m}\left(\mathbf r\right)=k_m\displaystyle\int_V\dfrac{\mathbf M\left(\mathbf r^{\prime}\right)\wedge\hat{\mathbf R}}{R^2}\ \mathrm{d}\tau^{\prime},&(2)\end{array} by the superposition principle, the vector potential outside a magnetized body must be the sum of the vector potentials due to free currents and magnetization. When applying the curl we obtain \begin{array}{cl}\boldsymbol\nabla\wedge\mathbf A=\boldsymbol\nabla\wedge\mathbf A_\text{l}+\boldsymbol\nabla\wedge\mathbf A_\text{m}&(3)\end{array}

The total magnetic field will result from applying the curl to the total vector potential (sup. pple. again), so that $\mathbf B=\boldsymbol\nabla\wedge\mathbf A$. If we apply the curl (with respect to the coordinates of $\mathbf r$) to $(2)$ we will obtain the magnetic field due to the magnetization of the material: \begin{equation}\boldsymbol\nabla\wedge\mathbf A_\text{m}=\boldsymbol\nabla\wedge\left(k_m\displaystyle\int_V\dfrac{\mathbf M\left(\mathbf r^{\prime}\right)\wedge\hat{\mathbf R}}{R^2}\ \mathrm{d}\tau^{\prime}\right)=k_m\displaystyle\int_V\boldsymbol\nabla\wedge\left(\mathbf M\left(\mathbf r^{\prime}\right)\wedge\dfrac{\hat{\mathbf R}}{R^2}\right)\ \mathrm{d}\tau^{\prime}.\end{equation} Expanding the integrand: \begin{equation}\boldsymbol\nabla\wedge\left(\mathbf M\left(\mathbf r^{\prime}\right)\wedge\dfrac{\hat{\mathbf R}}{R^2}\right)=\underbrace{\left(\mathbf M\cdot\boldsymbol\nabla\right)\dfrac{\hat{\mathbf R}}{R^2}}_{(\text{a})} -\underbrace{\left(\dfrac{\hat{\mathbf R}}{R^2}\cdot\boldsymbol\nabla\right)\mathbf M}_{(\text{b})}+\underbrace{\dfrac{\hat{\mathbf R}}{R^2}\left(\boldsymbol\nabla\cdot\mathbf M\right)}_{(\text{c})}-\underbrace{\mathbf M\left(\boldsymbol\nabla\cdot\dfrac{\hat{\mathbf R}}{R^2}\right)}_{(\text{d})}\end{equation}

Everything that derives from the vector magnetization is null because it only depends on $\mathbf r^{\prime}$, so $(\text{b})$ and $(\text{c})$ are canceled. The term $(\text{d})$ is the one that interests: \begin{equation}k_m\mathbf M\left(\boldsymbol\nabla\cdot\dfrac{\hat{\mathbf R}}{R^2}\right)=4\pi k_m \mathbf M\left(\mathbf r^{\prime}\right)\delta^3\left(\mathbf R\right)=\mu_0 \mathbf M\left(\mathbf r^{\prime}\right)\delta^3\left(\mathbf R\right)\end{equation}

I thought that the term $(\text{a})$ would be canceled out but it does not give me null: \begin{array}{rcl}\left(\mathbf M\cdot\boldsymbol\nabla\right)\dfrac{\hat{\mathbf R}}{R^2}&=&\displaystyle\sum_{i=1}^3M_i\frac{\partial }{\partial x_i}\displaystyle\sum_{j=1}^3\frac{R_j}{R^3}\mathbf e_j=\displaystyle\sum_{i,j=1}^3M_i\mathbf e_j\frac{\partial }{\partial x_i}\left(\frac{R_j}{R^3}\right)\\&=&\displaystyle\sum_{i,j=1}^3\dfrac{M_i\mathbf e_j}{R^6}\left[R^3\frac{\partial R_j}{\partial x_i}-R_j\frac{\partial R^3}{\partial x_i}\right]\end{array}

Separately (With $\mathbf R=\mathbf r-\mathbf r^\prime=R_1\hat{\mathbf e}_1+R_2\hat{\mathbf e}_2+R_3\hat{\mathbf e}_3$ and $R_i=x_i-x_i^\prime$): \begin{array}{rcl}\dfrac{\partial R_j}{\partial x_i}&=&\dfrac{\partial x_j}{\partial x_i}=\delta_{ij}\\\dfrac{\partial R^3}{\partial x_i}&=&\dfrac{\partial R^3}{\partial R}\dfrac{\partial R}{\partial x_i}=3R^2\cdot\dfrac{R_i}{R}=3RR_i\end{array} Substituting: \begin{array}{rcl}\left(\mathbf M\cdot\boldsymbol\nabla\right)\dfrac{\hat{\mathbf R}}{R^2}&=&\displaystyle\sum_{i,j=1}^3\dfrac{M_i\mathbf e_j}{R^6}\left[R^3\delta_{ij}-R_j3RR_i\right]=\displaystyle\sum_{i,j=1}^3\dfrac{M_i\mathbf e_j}{R^6}R^3\delta_{ij}-\displaystyle\sum_{i,j=1}^3\dfrac{M_i\mathbf e_j}{R^6}R_j3RR_i\\&=&\dfrac{1}{R^3}\displaystyle\sum_{i=1}^3M_i\mathbf e_i-\dfrac{3}{R^5}\displaystyle\sum_{i=1}^3M_iR_i\displaystyle\sum_{j=1}^3R_j\mathbf e_j=\dfrac{\mathbf M}{R^3}-\dfrac{3}{R^5}\left(\mathbf M\cdot\mathbf R\right)\mathbf R\\&=&\dfrac{1}{R^3}\left[\mathbf M-3\left(\mathbf M\cdot\hat{\mathbf R}\right)\hat{\mathbf R}\right]\end{array}

Substituting above and integrating (taking into account that $\mathbf m=\int_V\mathbf M\ \mathrm{d}\tau^\prime$) I obtain:

\begin{equation}\mathbf B_\text{m}=-\dfrac{k_m}{R^3}\left[3\left(\mathbf m\cdot\hat{\mathbf R}\right)\hat{\mathbf R}-\mathbf m\right]-\mu_0\mathbf M \end{equation} The first term coincides with the magnetic field of a magnetic dipole. I don't understand the reason it is there, in electrostatics we don't have the electric field of a electric dipole.

If $(\text{a})$ was null, the latter would only integrate the term $(\text{d})$ and obtain $\boldsymbol\nabla\wedge\mathbf A_\text{m}=-\mu_0\mathbf M\left(\mathbf r\right)$, so substituting on $(3)$ would be $\mathbf B+\mu_0\mathbf M=\boldsymbol\nabla\wedge\mathbf A_\text{l}$. But I'd need a minus sign there so that it would be $\mu_0\mathbf H$. Yes, I'm definetly sutck.

Well, life is hard and I do not get that, does anyone see the failure?

PS: Who did it, thanks for reading this tedious speech ;).

$\endgroup$
  • 1
    $\begingroup$ If you apply a Lorentz transformation to the electrical relation, you get the relation immediately. $\endgroup$ – my2cts Dec 28 '18 at 12:43
  • 1
    $\begingroup$ @David G. I think, in title the wronh sign. It should be H = B/\mu_0 - M $\endgroup$ – Sergio Dec 28 '18 at 14:19
  • 1
    $\begingroup$ My understanding is that's the definition of $\mathbf{H}$, similarly for $\mathbf{D}$. You can bring in higher order multi-poles into this, but they're usually really small. Jackson's textbook has a decent discussion of this. $\endgroup$ – Sean E. Lake Dec 28 '18 at 14:40
  • 2
    $\begingroup$ using the Helmholtz theorem (en.wikipedia.org/wiki/Helmholtz_decomposition) your question is worked out in detail in Brown: Magnetostatic Principles in Ferromagnetism, pp 18-25 $\endgroup$ – hyportnex Dec 28 '18 at 14:41
  • 1
    $\begingroup$ Under Lorentz boosts D, E and P transform into H, B, M respectively. $\endgroup$ – my2cts Dec 29 '18 at 23:45
0
$\begingroup$

I can go back to sleep calmly, after days of arduous search ... I found it! The calculations were not really bad, the additional term is due to the magnetic potential $V_\text{m}$ (the scalar, not the potential vector $\mathbf A$).

Whoever has been thinking about this like me, can consult López Rodríguez, V., Montoya Lirola, M. &Pancorbo Castro, M. (2016). Electromagnetismo II. Madrid: Universidad Nacional de Educación a Distancia. Tema 1. CAMPO MAGNÉTICO EN MATERIALES - 6.1 Potencial escalar magnético.

PS:Sorry, the only one I found was in spanish. I did not see it in any english textbooks. But, it has a derivation practically equal to mine.

Thank you very much to anyone who had the trouble of sending an answer. Happy New Year to everyone!

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.